CFD analyses of a radial fan for electric motor cooling. (December 2018) - Galloni, E.; Parisi, P.; Marignetti, F.; Volpe, G.
Highlights: A radial fan for electric motor cooling has been studied by means of CFD calculations. Fan performance's have been investigated considering the influence of both the impeller shape and the number of blades. The maximum value of the flow coefficient has been expressed as a function of the impeller aspect ratio. Mathematical relationships useful for the right sizing of a fan have been derived. Abstract: Fans are commonly used to cool electric motors. They can be mounted directly on the electric motor shaft providing a simple and inexpensive cooling system. The fan sizing is crucial to ensure safe operating temperatures of the electric motor. Referring to the self-ventilated motors, in this paper a numerical model has been developed and validated for a given radial fan. Afterwards, numerical analyses have been done in order to assess the performance of fans characterized by different shapes. Dimensionless characteristic curves have been calculated varying the wheel aspect ratio and the number of blades. Calculations show that, for a given blade number, the dimensionless flow capacity depends on the aspect ratio of the impeller. Furthermore, for a given geometry, there is an optimal number of blades that maximizes the flow rate processed by the fan. Results allow to obtain relationships useful to the right choice or sizing of such fluid machines.